(untitled) (ICEJ : Islamic Childhood Education Journal, 2022)
Abstract Given that children’s fine motor skills are very important, improvements are needed in terms of children’s fine motor development. Some of the activities carried out to develop or improve fine motor skills in early childhood include: folding paper, drawing with crayons, shaping and manipulating clay/wax/dough, painting with watercolors, playing collage, cutting, stringing objects with ropes/objects. (meronce), and sewing. The motor activity aims to train children’s motor coordination skills including eye and hand coordination which can be developed through play activities. Pattern sewing is one of the activities that can be done by early childhood as an effort to develop fine motor skills. This technical activity is a simple activity but can increase creativity, concentration, and distribution of children. In addition to the process that involves the activeness and thinking power of children, the results also provide satisfaction for children, because they produce quite interesting works. Abstrak Mengingat kemampuan motorik halus anak sangat penting maka diperlukan perbaikan dalam hal perkembangan motorik halus anak. beberapa kegiatan yang dilakukan untuk mengembangkan atau meningkatkan motorik halus anak usia dini diantaranya yaitu: meipat kertas, mengambar dengan krayon, membentuk dan memanipulasi dari tanah liat/ lilin/ adonan, melukis dengan cat air, bermain kolase, menggunting, merangkai benda dengan tali/ benda (meronce), dan menjahit. Aktivitas motorik tersebut bertujuan untuk melatih keterampilan koordinasi motorik anak diantaranya koordinasi mata dan tangan yang dapat dikembangkan melalui kegiatan bermain. Kegiatan menjahit pola merupakan salah satu kegiatan yang dapat dilakukan anak usia dini sebagai upaya untuk mengembangkan motorik halus. Kegiatan teknik ini merupakan kegiatan sederhana namun dapat meningkatkan kreativitas, konsentrasi, dan kesebaran anak. selain prosesnya yang melibatkan keaktifan dan daya fikir anak, hasilnya juga memberikan kepuasan tersendiri bagi anak, karena menghasilkan karya yang cukup menarik.